Perancangan UI/UX Sistem Informasi Pemesanan Jasa betukang.id Menggunakan Metode Design Thinking - Ardi Ardi; Dewi Yanti; Istikoma Istikoma (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
Startups in Indonesia are growing rapidly due to the increasing number of internet users and people's increasing purchasing power, atransaction activity carried out through startup businesses also contributes to Indonesia's economic growth, , therefore PT Betukang Sejahtera Indonesia is required to be ready to compete both in terms of services and information systems provided through applications, betukang.id is an application that provides various types of carpentry services, this study aims to redesign the User Interface (UI) and User Experience (UX), Design thinking methodUsed to produce an application display that makes it easier for users to order services, starting from the stage (empathize) to define the problem, the stage (define) formulating the problem, (ideate) collecting ideas, the stage (prototype) making application design, tested at the stage (test) using usability tools maze.co, then evaluating the results of usability testing using the method System Usability Scale (SUS) to 40 user respondents betukang.id obtained an average score of 83, thus it can be concluded that the UI / UX design of the ordering information system in betukang.id application using the Design thinking method can be used easily based on the results of SUS.